Professor Volodymyr Semenovych Kulchytsky – outstanding lawyer scientist - Kravchuk, Mykola (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article highlights the family heritage and the prerequisites for the formation of the personality of Professor Volodymyr Semenovych Kulchytskyi during his primary and secondary education, the influence of various factors on his development as a personality in childhood is revealed. The main stages of the scientific life of Professor V. S. Kulchytsky and his contribution to the development of his own scientific school, his scientific interests and the practical development of their results are outlined. The main scientific achievements were considered and an assessment of his scientific followers was carried out. The description of his activity is presented through the prism of the assessment of personal contribution by colleagues in joint work and graduate students. His contribution to the formation and development of the independent, cathedral, sovereign Ukrainian state and his state awards for social, political, educational and scientific activities are reflected.It has been confirmed that Professor Volodymyr Semenovych Kulchytskyi is a recognized authoritative scholar-lawyer, an outstanding head of the Lviv Historical School of Law, a Ukrainian patriot-statesman, an unsurpassed teacher and mentor. This is a person whose name has forever entered into the heritage of Ukrainian historical and legal science.